A prospective randomized study of the efficacy and cost-effectiveness of high and low dose regimens of I-131 treatment in hyperthyroidism - Pawana Pusuwan (2018)
Objective: To compare the efficacy and cost-effectiveness of high and low dose regimens of I-131 treatment in patients with hyperthyroidism. Material and Method: One hundred fifty patients with proven hyperthyroidism were randomly allocated into the high (74 patients) and low (76 patients) dose regimen of I-131 treatment. Four patients of the high dose group and one patient of the low dose group were excluded because of lost follow-up. A gland-specific dosage was calculated on the estimated weight of thyroid gland and 24-hour I-131 uptake. The high and low I-131 dose regimens were 150 μCi/gm and 100 μCi/gm, respectively. The first mean radioiodine activity administered to the high and low dose group was 10.2 and 8 mCi, respectively. Repeated treatment was given to 25 patients of the high dose group and 40 patients of the low dose group. Clinical outcome and calculated costs for outpatient attendances, and laboratory tests together with initial and subsequent treatments were evaluated for one year after I-131 treatment. Elimination of hyperthyroidism that resulted in either euthyroidism or hypothyroidism was classified as therapeutic success. The cost effectiveness was also compared. Results: At 6 months after treatment, 45 (64.3%) patients receiving high dose and 59 (78.7%) patients receiving low dose were hyperthyroidism. Clinical outcome at one year showed persistence of hyperthyroidism in 21 (30%) patients of the high dose regimen and 36 (48%) patients of the low dose regimen. At one year post treatment, it was demonstrated that the high dose regimen could eliminate hyperthyroidism in a significantly shorter time than the low dose regimen, i.e., 259.6 days and 305.5 days, respectively, p = 0.008). For the persistent hyperthyroid patients, the average total cost o f treatment in the low dose group was significantly higher than that of the high dose group, i.e., 13,422.78 baht and 10,942.79 baht, respectively; p = 0.050) Conclusion: A high dose regimen of radioactive iodine treatment is more effective than the low dose regimen. The successful outcome of a high dose regimen occurred significantly earlier than that of the low dose regimen. For the persistent hyperthyroid patients, the average total cost in the low dose group was significantly higher than that of the high dose group.